The good entrance design approach of the shopping malls in Ipoh, Perak / Balqis Amirah Abdul Talib - Abdul Talib, Balqis Amirah (2014)
The broad objective of this qualitative research is to study about the good entrance design approach for a shopping mall and the criteria gained from the observations on its elements and features, which are the provision of the good appearance, the drop-off area and the pedestrian walkway and linkages for the shopping malls. The scope of the study is focusing on the entrance design approach of the shopping malls in Ipoh, Perak which are the AEON Station 18, the Angsana Ipoh Mall and the Ipoh Parade. There are five methods of studying about this topic which are the background study, observations, literature review, data collections and its analysis.